1993
DOI: 10.1042/bj2910641
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and inducible profile of glutathione S-transferase subunits in biliary epithelial cells and hepatocytes isolated from rat liver

Abstract: The constitutive and inducible cytosolic glutathione S-transferase (EC 2.5.1.18) subunit compositions of parenchymal cells (hepatocytes) and biliary epithelial cells (BEC) from rat liver have been quantitatively analysed using reverse-phase h.p.l.c. Hepatocytes, analysed in the absence of non-parenchymal cells, expressed constitutively the following subunits, in order of their concentration: 3, 4, 2, 1a, 1b, 8, 6 and 10. BEC express constitutively only four of the GST subunits expressed by hepatocytes and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Other investigators have shown that the presence of high intracellular concentrations of GST facilitates net uptake of nonsubstrate ligands into the hepatocyte by decreasing ligand efflux from the cell (1,12,59,60), although these observations have been challenged (61). It is notable that various xenobiotic compounds have been demonstrated to modulate GST gene expression in a host of tissues, including the liver (44,62,63). Specific evidence in support of the potential regulation of GST expression by bilirubin is derived from the finding that erythrocytes of infants with neonatal jaundice (unconjugated hyperbilirubinemia) exhibit markedly elevated GST activity as compared with nonjaundiced newborns (64).…”
Section: Resultsmentioning
confidence: 97%
“…Other investigators have shown that the presence of high intracellular concentrations of GST facilitates net uptake of nonsubstrate ligands into the hepatocyte by decreasing ligand efflux from the cell (1,12,59,60), although these observations have been challenged (61). It is notable that various xenobiotic compounds have been demonstrated to modulate GST gene expression in a host of tissues, including the liver (44,62,63). Specific evidence in support of the potential regulation of GST expression by bilirubin is derived from the finding that erythrocytes of infants with neonatal jaundice (unconjugated hyperbilirubinemia) exhibit markedly elevated GST activity as compared with nonjaundiced newborns (64).…”
Section: Resultsmentioning
confidence: 97%
“…GST (GST) was not detected in liver, irrespective of the treatment. Normally, only traces of this isoform are found in hepatic cytosol, mostly because of contamination with biliary epithelial cells (Parola et al, 1993). Intestinal content of the different GST classes was not …”
Section: Expression and Activity Of Gstmentioning
confidence: 99%
“…Among the reductive substances that protect cells from oxidative stress, glutathione is a representative endogenous cytoprotective molecule and may protect biliary epithelial cells (BECs) from ROS as part of an antioxidant system 20,21 . Glutathione‐S‐transferase (GST) generates intracellular glutathione, and GST‐pi is a major subunit of biliary epithelial GST 22 . Recently, it was reported that GST‐pi expression was markedly reduced in the damaged bile ducts of PBC patients, reflecting a reduction of intracellular glutathione 23 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Glutathione-S-transferase (GST) generates intracellular glutathione, and GST-pi is a major subunit of biliary epithelial GST. 22 Recently, it was reported that GST-pi expression was markedly reduced in the damaged bile ducts of PBC patients, reflecting a reduction of intracellular glutathione. 23 This suggests that the intracellular imbalance of oxidative stress and the antioxidant system may lead to the bile duct damage seen in PBC patients.…”
Section: Introductionmentioning
confidence: 99%